ANALISIS VARIABEL-VARIABEL KEPUASAN PELANGGAN (STUDI KASUS PT. BANK SYARIAH MANDIRI) - Imron Rosyadi (Jurnal Manajemen FE-UB, 2019)
This study aims to determine the extent of the influence of service quality, company imageon customer loyalty through customer satisfaction at PT. Bank Syariah Mandiri Jakarta ThamrinBranch.The data used in this study were primary data collected from respondents' answers basedon the questionnaire given, as many as 94 people. Data processing method uses the path analysismethod (Path Analysis) with the help of SPSS version 21.0. Statistical testing uses the individualparameter significance test (t test) and simultaneous significance test (F test).The results showed that simultaneous service quality variables, company image andcustomer satisfaction significantly influence customer loyalty. Partially shows that analysis 1:service quality variables significantly influence customer loyalty, while analysis 2: companyimage variables significantly influence customer loyalty and analysis 3: customer satisfactionvariables significantly influence customer loyalty performance.Keywords: Service Quality, Company Image, Customer Satisfaction and Customer Loyalty